2021
DOI: 10.3389/fnins.2021.766826
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Exposure to a Human-Relevant Polychlorinated Biphenyl Mixture Causes Behavioral Phenotypes That Vary by Sex and Genotype in Juvenile Mice Expressing Human Mutations That Modulate Neuronal Calcium

Abstract: Polychlorinated biphenyls (PCBs) are putative environmental risks for neurodevelopmental disorders. Here, we tested two hypotheses: (1) developmental exposure to a human-relevant PCB mixture causes behavioral phenotypes relevant to neurodevelopmental disorders; and (2) expression of human mutations that dysregulate neuronal Ca2+ homeostasis influence sensitivity to behavioral effects of developmental PCB exposures. To test these hypotheses, we used mice that expressed a gain-of-function mutation (T4826I) in ry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 102 publications
(144 reference statements)
0
26
0
Order By: Relevance
“…Furthermore, in the MARBLES cohort, PCBs were detected in the serum of the pregnant mothers at levels that were experimentally shown to impact neurodevelopmental processes in model systems ( Sethi et al, 2017a , 2019 ). When C57BL/6J mice were prenatally exposed to the MARBLES PCB mixture at 0.1 or 1.0 mg/kg/day through maternal diet, postnatal brain (~1 month old) showed PCB levels comparable to those reported in human samples ( Lanting et al, 1998 ; Mitchell et al, 2012 ), coincident with changes in the dendritic morphology of hippocampal and cortical pyramidal neurons and changes in ASD-relevant behaviors ( Keil Stietz et al, 2021 ; Sethi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 82%
“…Furthermore, in the MARBLES cohort, PCBs were detected in the serum of the pregnant mothers at levels that were experimentally shown to impact neurodevelopmental processes in model systems ( Sethi et al, 2017a , 2019 ). When C57BL/6J mice were prenatally exposed to the MARBLES PCB mixture at 0.1 or 1.0 mg/kg/day through maternal diet, postnatal brain (~1 month old) showed PCB levels comparable to those reported in human samples ( Lanting et al, 1998 ; Mitchell et al, 2012 ), coincident with changes in the dendritic morphology of hippocampal and cortical pyramidal neurons and changes in ASD-relevant behaviors ( Keil Stietz et al, 2021 ; Sethi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 82%
“…In that study, dams were orally administered a PCB mixture from 2-weeks prior to mating until pup weaning (P21). Ultrasonic vocalizations at P7 were diminished in all three mutant pup genotypes while both male and female T4826I and DM pups exhibited high spontaneous grooming behavior ( Sethi et al, 2021 ). Further, studies from the same group found that PCBs promote synaptogenesis in cultured hippocampal neurons, as evidenced by increased dendritic spines and miniature excitatory postsynaptic currents ( Lesiak et al, 2014 ).…”
Section: Autism Spectrum Disorders (Asd)mentioning
confidence: 97%
“… Sethi et al (2021) conducted a follow-up study to understand the interaction of Ryr1 and Fmr1 and polychlorinated-biphenyls (PCBs) exposure in ASD-like behaviors ( Sethi et al, 2021 ). PCBs comprise environmental contaminants with established neurodevelopmental consequences that exert their neurotoxic effects by binding to the RyRs ( Pessah et al, 2010 ).…”
Section: Autism Spectrum Disorders (Asd)mentioning
confidence: 99%
“…We also investigated metabolites of PCB 28 in the liver from a mouse exposed during gestation and lactation to a PCB mixture. Based on the MS transition m / z 286 → 243, we identified three trichlorinated MeO-PCB peaks (peaks 1, 2, and 3) corresponding to monohydroxylated metabolites of PCB 28 (Figure a). Based on the experimental and predicted RRT and MS/MS data, the weighted rank scores of all possible MeO-PCB 28 candidates (Figure S10) were calculated for the three MeO-PCB 28 peaks (Figure b).…”
Section: Resultsmentioning
confidence: 99%